Physiological and Transcriptomic Variability Indicative of Differences in Key Functions Within a Single Coral Colony - Drake, Jeana L.; Malik, Assaf; Popovits, Yotam; Yosef, Oshra; Shemesh, Eli; Stolarski, Jarosław; Tchernov, Dan; Sher, Daniel; Mass, Tali (Frontiers in Marine Science, 2021)
Polyps in different locations on individual stony coral colonies experience variation in numerous environmental conditions including flow and light, potentially leading to transcriptional and physiological differences across the colony. Here, we describe high-resolution tissue and skeleton measurements and differential gene expression from multiple locations within a single colony of Stylophora pistillata, aiming to relate these to environmental gradients across the coral colony. We observed broad transcriptional responses in both the host and photosymbiont in response to height above the substrate, cardinal direction, and, most strongly, location along the branch axis. Specifically, several key physiological processes in the host appear more active toward branch tips including several metabolic pathways, toxin production for prey capture or defense, and biomolecular mechanisms of biomineralization. Further, the increase in gene expression related to these processes toward branch tips is conserved between S. pistillata and Acropora spp. The photosymbiont appears to respond transcriptionally to relative light intensity along the branch and due to cardinal direction. These differential responses were observed across the colony despite its genetic homogeneity and likely inter-polyp communication. While not a classical division of labor, each part of the colony appears to have distinct functional roles related to polyps’ differential exposure to environmental conditions.